The vote [videorecording (DVD)] - Ferrari, Michelle; Burton, Kate (PBS, 2020)
One hundred years after the passage of the Nineteenth Amendment, it tells the dramatic culmination story of the hard-fought campaign waged by American women for the right to vote, a transformative cultural and political movement that resulted in the largest expansion of voting rights in US history.